Pendidikan Karakter Pada Anak Usia Dini Melalui Model Pembelajaran Sentra - Niken Ristianah; M. Munir (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2022)
Character education is one of the important aspects for the next generation of the Indonesian nation so that character education must be given along with the intellectual development of children. Children's character can be formed well if in the process of child development there is sufficient space so that children can express themselves freely. This is closely related to character building, where children's character education must be formed from an early age. This is because early childhood is at a golden age which we must really stimulate and stimulate to the fullest in all aspects of its development. Building early childhood education is different from building other levels of education, because this education provides opportunities for children to be able to enjoy their world, namely the main world. Play is a means for children to learn so that it can be said that early childhood learning is playing. By playing children are stimulated to develop in general, both physical, motor, cognitive, language, artistic, social, emotional development and through playing children will feel happy and comfortable at school. The strategy used is the learning center model. Learning strategies are carried out in circles and play centers. Circle is when the teacher and children sit in a circle to provide a foothold for children what to do before and before playing. The play center is a zone for children to play, which is equipped with game tools that function to develop the full potential of children in various aspects of their overall development